2015
DOI: 10.1002/zaac.201500255
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Structures of CuII 15‐Metallacrown‐5 Complexes with Encapsulated CaII, PrIII and NdIII Ions

Abstract: Abstract.Three (3) (opicHA = 2-picolinehydroxamic acid) were synthesized in order to retrace structural trends caused by the change of the ionic radius of the central metal ion as well as to assess the effect of the axial ligands on the arrangement of metallacrowns. The complexes were characterized by elemental analysis, ESI-mass spectrometry, IR spectroscopy, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The separation between the copper (II) cations is 5.2949 (4) Å . The equatorial Cu-N and Cu-O distances are typical of those for copper(II) complexes with hydroxamate and oxime donor groups (Buvailo et al, 2012;Duda et al, 1997;Pavlishchuk et al, 2011b;Safyanova et al, 2015, Table 1). The elongated apical bond, Cu1-O2 (2.2516 (16) Å ), compared to the Cu-O and Cu-N distances in the equatorial plane that range from 1.9848 (16) to 1.9966 (19) Å , Table 1, is most likely due to Jahn-Teller distortion.…”
Section: Structural Commentarymentioning
confidence: 81%
“…The separation between the copper (II) cations is 5.2949 (4) Å . The equatorial Cu-N and Cu-O distances are typical of those for copper(II) complexes with hydroxamate and oxime donor groups (Buvailo et al, 2012;Duda et al, 1997;Pavlishchuk et al, 2011b;Safyanova et al, 2015, Table 1). The elongated apical bond, Cu1-O2 (2.2516 (16) Å ), compared to the Cu-O and Cu-N distances in the equatorial plane that range from 1.9848 (16) to 1.9966 (19) Å , Table 1, is most likely due to Jahn-Teller distortion.…”
Section: Structural Commentarymentioning
confidence: 81%
“…The coordination ability of hydroxamic acids has led to their extensive use in coordination and supramolecular chemistry (Ś wią tek-Kozłowska et al, 2000;Dobosz et al, 1999). In particular, over the past two decades they have often been used as frameworks of metallacrowns (Golenya et al, 2012a;Safyanova et al, 2015;Stemmler et al, 1999;Jankolovits et al, 2013a,b) and as building blocks of coordination polymers (Gumienna-Kontecka et al, 2007;Golenya et al, 2014;Pavlishchuk et al, 2010Pavlishchuk et al, , 2011. They have also been studied intensively in biology and medicine due to their various biological activities, especially their metal-chelating ability and inhibition of a series of metalloenzymes (Codd, 2008;Griffith et al, 2005;Marmion et al, 2013).…”
Section: Chemical Contextmentioning
confidence: 99%
“…A search of the Cambridge Structural Database (Groom et al, 2016) for metal complexes based on N-hydroxypicolinamide revealed the crystal structures of over 20 compounds, mostly belonging to the metallacrown (MC) family. In particular, heterometallic copper(II) 15-metallacrown-5 complexes with encapsulated Gd III and Eu III ions (Stemmler et al, 1999), Ca 2+ , Pr 3+ and Nd 3+ ions (Safyanova et al, 2015), UO 2 2+ (Stemmler et al, 1996), and Pb 2+ and Hg 2+ ions (Seda et al, 2007; Saf'yanova et al, 2014) have been structurally characterized. Nickel(II) 15-metallacrown-5 complexes with Eu 3+ (Jankolo-vits et al, 2013b), Sm 3+ and Pb 2+ ions (Seda et al, 2006a) in the central cavity have also been synthesized and structurally characterized.…”
Section: Database Surveymentioning
confidence: 99%
“…They are widely used in the preparation of metallacrowns (Golenya et al, 2012a;Gumienna-Kontecka et al, 2013;Safyanova et al, 2015) and as building blocks for synthesis of metal-organic frameworks and coordination polymers (Gumienna-Kontecka et al, 2007;Golenya et al, 2014;Pavlishchuk et al, 2010Pavlishchuk et al, , 2011.…”
Section: Chemical Contextmentioning
confidence: 99%